Web development and design foundations with HTML5 - Felke-Morris, Terry (Pearson Education Limited, 2017)
For courses in web development and design. A Comprehensive, Well-Rounded Intro to Web Development and Design Updated and expanded in this Eighth Edition, Web Development and Design Foundations with HTML5 presents a comprehensive introduction to the development of effective web sites. Intended for beginning web development courses, the text relates both the necessary hard skills (such as HTML5, CSS, and JavaScript) and soft skills (design, e-commerce, and promotion strategies) considered fundamental to contemporary web development. An emphasis on hands-on practice guides students, as the text